Leadership and Critical Decision-Making in High-Risk Search and Rescue Operations at the Ambon Search and Rescue Office - Kusworo Kusworo; Abdul Haris Achadi; Jeremy Putra pratama (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Indonesia recorded 2,560 search and rescue (SAR) incidents in 2024, underscoring the need for leaders who can make rapid yet safety centered decisions in hazardous environments. This study examines leadership in critical decision making during high risk SAR operations through a qualitative case study of a man overboard incident handled by the Ambon Search and Rescue Office. Data were collected through in depth interviews with key informants, field observation, and review of operational documents, then analyzed using iterative reduction, descriptive synthesis, and triangulation. The decision chronology shows that operational authority was concentrated at the field commander (Dantim), with coordination intended to supply situational input before actions were authorized. However, decision quality was constrained by gaps in information synchronization across teams and command levels, particularly regarding dive planning, reporting, and validation of high risk actions. Operational stressors, including time pressure, extreme sea conditions, limited resources, external demands from family and media, and emotional strain after a teammate loss, influenced risk appraisal and could narrow attention toward mission urgency. Post operation evaluation indicated fatigue and equipment malfunction as proximate contributors to the rescuer’s fatal incident, alongside weaknesses in briefing and debriefing discipline. Strengthening rescuer safety requires clearer communication pathways for critical decisions, structured briefings and debriefings, fatigue management, equipment reliability controls, and stress informed decision training within a clear command accountability structure.